(untitled) (Community Based Medical Journal, 2015)
To determine the distribution of common medical conditions related to stroke among Bangladeshi patients. This is an observational study. It involved 336 stroke patients from different medicine wards in Dhaka Medical College Hospital from July 2012 to June 2013. We assessed some common established medical conditions observed among stroke patients e.g. age, sex, family history, hypertension, diabetes, ischemic heart disease, smoking, obesity, dyslipidaemia, alcoholism, use of oral contraceptive pill, etc. A predesigned check list was used for data collection. Among 336 patients, most of the stroke events occurred after the age of forty (82.3%) and the ischemic stroke (72%) being the most common. Other than the non-modifiable risk factors (advancing age, sex, Family history of stroke) hypertension was the most common factor found in relation to stroke patients (57.6%) followed by smoking (44.6%), tobacco use (24.3%), OCP use in female (40% of female stroke), diabetes (23%), ischemic heart disease (17.1%), obesity (10.6%) and dyslipidaemia (5.3%). Stroke is common after the age of forty. Ischemic events are the commonest type of stroke. Hypertension, smoking, diabetes, tobacco use, and ischemic heart disease were five most principal conditions associated with stroke. CBMJ 2015 July: Vol. 04 No. 02 P: 13-19